Study on spectroscopic properties and effects of tungsten ions in 2Bi2O3-3GeO2/SiO2 glasses. (April 2017) - Yu, Pingsheng; Su, Liangbi; Cheng, Junhua; Zhang, Xia; Xu, Jun
Abstract: The 2Bi2 O3 -3GeO2 /SiO2 glass samples have been prepared by the conventional melt quenching technique. XRD patterns, absorption spectra, excitation-emission spectra and Raman measurements were utilized to characterize the synthesized glasses. When substitute SiO2 for GeO2, the 0.4Bi2 O3 -(0.4-0.1)GeO2 -(0.2–0.5)SiO2 glasses exhibit strong emission centered at about 475 nm (under 300 nm excitation), and the decay constants are within the scope of 20–40 ns. W doping into 2Bi2 O3 -3SiO2 glass could increase the emission intensity of 470 nm, and the W-doped 2Bi2 O3 -3SiO2 glass has shown another emission at about 433 nm with much shorter decay time (near 10 ns). The 2Bi2 O3 -3GeO2 /SiO2 glass system could be the possible candidate for scintillator in high energy physics applications. Highlights: The Bi2 O3 -3GeO2 /SiO2 glasses exhibit strong emission centered at about 475 nm, and the decay constants are within the scope of 20–40 ns. W-doped 2Bi2 O3 -3SiO2 glass shows emission at about 433 nm with much shorter decay time (near 10 ns). W doping into 2Bi2 O3 -3SiO2 glass could increase the emission intensity of 470 nm.